2020
DOI: 10.1371/journal.pone.0243571
|View full text |Cite
|
Sign up to set email alerts
|

Synergies between urban heat island and heat waves in Seoul: The role of wind speed and land use characteristics

Abstract: The effects of heat waves (HW) are more pronounced in urban areas than in rural areas due to the additive effect of the urban heat island (UHI) phenomenon. However, the synergies between UHI and HW are still an open scientific question and have only been quantified for a few metropolitan cities. In the current study, we explore the synergies between UHI and HW in Seoul city. We consider summertime data from two non-consecutive years (i.e., 2012 and 2016) and ten automatic weather stations. Our results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 61 publications
(78 reference statements)
1
42
0
Order By: Relevance
“…Li et al (2015) revealed that the UHII is enhanced during HW periods compared to non-HW (NHW) periods in Beijing. Also, consistent synergies between UHIs and HWs have been reported in western Sydney (Khan et al, 2020), Seoul (Ngarambe et al, 2020), Singapore (Mughal et al, 2020), and Rome (Zinzi et al, 2020). Regarding the factors modulating UHIs and HWs, they are complex and vary both spatially and temporally, but can broadly be categorized into natural-type factors (local topography, synoptic weather, meteorological factors such as wind speed, cloud cover, relative humidity, etc.)…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Li et al (2015) revealed that the UHII is enhanced during HW periods compared to non-HW (NHW) periods in Beijing. Also, consistent synergies between UHIs and HWs have been reported in western Sydney (Khan et al, 2020), Seoul (Ngarambe et al, 2020), Singapore (Mughal et al, 2020), and Rome (Zinzi et al, 2020). Regarding the factors modulating UHIs and HWs, they are complex and vary both spatially and temporally, but can broadly be categorized into natural-type factors (local topography, synoptic weather, meteorological factors such as wind speed, cloud cover, relative humidity, etc.)…”
Section: Introductionmentioning
confidence: 75%
“…and anthropogenic-type factors (i.e., anthropogenic activities such as emissions of anthropogenic heat and aerosols, as well as land use/land cover changes related to rapid urbanization, etc.) (Li et al, 2015;Ngarambe et al, 2020;Zinzi et al, 2020). To some extent, buildings, the surface composition, and pavements also affect the exchanges of heat in cities (Shahidan et al, 2012;Wong et al, 2017;He, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While the repercussions of urban overheating are multifaceted and naturally diverse, they can be subtly grouped into three broad categories: (I) direct impact on urban dwellers in terms of exerted thermal stress, especially in the summertime or periods of extreme heat events and which results in increased heat-related thermal discomfort, mortalities, and morbidities ( Founda and Santamouris, 2017 ; He et al., 2021 ; Ngarambe et al., 2020 ), (II) heightened urban air pollution levels resulting from synergistic interactions between UHI-related elevated temperatures and atmospheric pollutants often fueled by complex photochemical processes ( Cao et al., 2016 ; Ngarambe et al., 2021 ; Ulpiani, 2021 ), and (III) a serious impact on the energy demand of cities; they increase the cooling load and partially decrease the heating load ( Li et al., 2019 ; Santamouris, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Li, Y et al used the surface and vegetation characteristics of the region around Berlin (Germany), and ran the urban climate model driven by the same lateral climate conditions in order to simulate the urban climate of various generated cities under the same weather conditions [ 20 ]. Ngarambe J et al explored the synergies between urban heat island and heat waves in Seoul city, and showed that UHI was more intense during heat waves periods than non-heat wave periods and the synergies were relatively more intense in densely built areas and under low wind speed conditions [ 21 ]. Yang J et al found that the growing season of vegetation in urban areas was significantly different from that in rural areas, which have generally been attributed to the influence of the urban heat island effect on vegetation phenology along the urban–rural gradient [ 22 ].…”
Section: Introductionmentioning
confidence: 99%